2020
DOI: 10.1016/j.joule.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Global Techno-Economic Performance of Bifacial and Tracking Photovoltaic Systems

Abstract: This work performs a comprehensive techno-economic analysis worldwide for photovoltaic systems using a combination of bifacial modules and single-and dual-axis trackers. We find that single-axis trackers with bifacial modules achieve the lowest LCOE in the majority of locations (16% reduction on average). Yield is boosted by 35% by using bifacial modules with single-axis trackers and by 40% in combination with dual-axis trackers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 35 publications
(43 reference statements)
0
51
0
2
Order By: Relevance
“…Similar dynamic PV systems were fabricated with a-Si PV cells and c-Si PV cells, respectively, in [112], and it was interesting that a-Si PV cells presented higher actual efficiency. According to a study reported in [113], the cost for fixed-tilt PV structures was USD 0.07 per watt output power, USD 0.12 per watt for the adjustable PV structures in one axis and USD 0.40 per watt for the two-axes ones [113].…”
Section: Optimization Of Location Azimuth and Tiltmentioning
confidence: 99%
“…Similar dynamic PV systems were fabricated with a-Si PV cells and c-Si PV cells, respectively, in [112], and it was interesting that a-Si PV cells presented higher actual efficiency. According to a study reported in [113], the cost for fixed-tilt PV structures was USD 0.07 per watt output power, USD 0.12 per watt for the adjustable PV structures in one axis and USD 0.40 per watt for the two-axes ones [113].…”
Section: Optimization Of Location Azimuth and Tiltmentioning
confidence: 99%
“…En el caso de los sistemas fotovoltaicos (SFV) es posible la optimización de etapas funcionales, en término de variables independientes, tal es el caso de la irradiancia, potencia recibida por unidad de superficie, y temperatura de los módulos, dando lugar a combinaciones de métodos de optimización [11][12]. En esta área se ha detectado la necesidad de un modelo matemático que incorpore los parámetros del sistema, describa los componentes y su comportamiento, con el objetivo de definir el control dinámico aplicando coeficientes adaptativos, a partir de la identificación de correspondencia entre cada una de los subsistemas.…”
Section: Introductionunclassified
“…Para el MPP, donde se relacionan parámetros como la irradiancia, temperatura y carga equivalente el generador fotovoltaico, se requiere un algoritmo de seguimiento[11],[19]. La reconfiguración dinámica permite mejorar el rendimiento del arreglo fotovoltaico, a través de la reducción de las pérdidas Joule.…”
unclassified
“…Bifacial PV has potential to reach the lowest levelised cost of energy ( LCOE ) of any commercially available PV technology because such bifacial energy gains are achievable using the same land area that is used for monofacial PV designs while maintaining comparable upfront costs [9, 10]. A study by Rodriguez‐Gallegos et al [11] assessed the economics of different PV designs and found that bifacial PV on single‐axis trackers achieves the lowest LCOE for >90% of the world's land area.…”
Section: Introductionmentioning
confidence: 99%